(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
Biomass transfer using fertiliser tree species is a more sustainable means for maintaining nutrient balances in maize based production systems. This research investigated the combined effects of incorporation of leafy biomass of fertilizer trees as organic fertilizer and urea as inorganic fertiliser for sustainable food production viz-a-viz maize-based crop in semi-arid, Nigeria. The experiment was laid out as 3 x 4 x 2 factorial in a split-split plot design with three replicates. Data were analysed using Analysis of Variance (ANOVA) at p =.05. Albizia lebbeck amended plots consistently had significantly higher values in 2014, 2015 and combined means (12.8 kg ha-1, 13 kg ha-1, 12.9 kg ha1) of cob length, (345.8 kg ha-1, 311.8 kg ha-1, 328.8 kg ha-1) of grains per cob and grain yield (2097.3 kg ha-1, 1667.7 kg ha-1, 1881.9 kg ha-1) throughout the cropping seasons and combined effect respectively compared to Parkia biglobosa. Positive significant correlation was experienced between the growth and yield components. Inclusion of nitrogen fertilizer and fertilizer trees improved the production of these maize varieties compared to control. It is therefore concluded that incorporation of Albizia lebbeck with up to 40 kg N ha-1 rate of nitrogen fertilizer into the soil improved its quality for better yield of both 2009 EVAT and DMR-ESR-7 maize varieties.